Implementation of green harvesting in the Sicilian wine industry: Effects on the cooperative system - Antonino Galati; Valeria Borsellino; Maria Crescimanno; Gaetano Pisano; Emanuele Schimmenti (Wine Economics and Policy, 2015)
This paper contributes to assessing the effectiveness of the GH measure to contribute in reducing the supply of wine grapes, and thus contrasting the fall of wine prices in those years when especially abundant productions are expected. By analysing the application of this measure to the Sicilian wine sector during the three-year period (2010-2012), we assess its effects on the regional wine cooperative system. The results from the analysis of the statistical data show that the GH measure was successful in terms of the number of applications, the supported area and financial expenditures, and contributed with other factors to determining a reduction in wine grape production. The empirical survey shows that GH has been contributing to contrast the fall of wine prices in this region and helping the recovery of the wine market. However, an increase in operating costs as well as difficulties in the planning activities of the cooperatives has been recorded.
Keywords: 330; CMO for wine; Cooperative system; Ex-ante market crisis measure